Robotics in Dentistry: A Review (Academia Journal of Medicine, 2024)
In recent years, robotics has emerged as a transformative force in the field  of dentistry, revolutionizing many aspects of clinical practice and advancing  patient care. This review provides an overview of the current state and future  prospects of robotics in dentistry, focusing on applications such as robotic assisted surgery, automated orthodontic procedures, and precision diagnostics.  Highlighting technological advancements, we examine how robotics enhances  precision, reduces procedural time, and increases safety in dental procedures.  Additionally, the review addresses challenges such as high costs, the need for  specialized training, and ethical considerations surrounding robotic integration  into dental practices. By analyzing current research, this article aims to present  a comprehensive understanding of the benefits, limitations, and impact of  robotics in dental care. Future prospects and innovations are also discussed,  paving the way for an increasingly automated and efficient dental industry.
Keywords: Dental Technology; Robotics; Dental Automation